Implementasi Model Pembelajaran Kooperatif Tipe Group Investigasi (GI) Berbasis Sigil Terhadap Motivasi Belajar Siswa Kelas X IPA SMA - Irwandi Irwandi; Welyta Wilhotama; Merri Sri Hartati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine the effect of the sigil-based investigative group (GI) type cooperative learning model on the learning motivation of class X Science students at SMA Negeri 6 Seluma Regency. This research method uses a quasi-experimental design with a research design in the form of a Non-Randomized Control-Group Pretest-Posttest Design. The data analysis technique for this research uses the One-Sample Kolmogorov-Smirnov normality test, which is then tested for homogeneity using Levene Statistics. After it is known that the data is normally distributed and homogeneous, a data analysis test is carried out using the T test. The research results show that the p-value obtained is of 0.000. In conclusion, there is an influence of the sigil-based investigative group (GI) type cooperative learning model on the learning motivation of class X Science students at SMA Negeri 6 Seluma Regency. Keywords: Investigation Group, Learning Motivation, Sigil